Missense Variant in MAPK Inactivator PTPN5 Is Associated with Decreased Severity of Post-Burn Hypertrophic Scarring - Sood, Ravi F. (PLoS One, 2016)
BACKGROUND: Hypertrophic scarring (HTS) is hypothesized to have a genetic mechanism, yet its genetic determinants are largely unknown. The mitogen-activated protein kinase (MAPK) pathways are important mediators of inflammatory signaling, and experimental evidence implicates MAPKs in HTS formation. We hypothesized that single-nucleotide polymorphisms (SNPs) in MAPK-pathway genes would be associated with severity of post-burn HTS. METHODS: We analyzed data from a prospective-cohort genome-wide association study of post-burn HTS. We included subjects with deep-partial-thickness burns admitted to our center who provided blood for genotyping and had at least one Vancouver Scar Scale (VSS) assessment. After adjusting for HTS risk factors and population stratification, we tested MAPK-pathway gene SNPs for association with the four VSS variables in a joint regression model. In addition to individual-SNP analysis, we performed gene-based association testing. RESULTS: Our study population consisted of 538 adults (median age 40 years) who were predominantly White (76%) males (71%) admitted to our center from 2007–2014 with small-to-moderate-sized burns (median burn size 6% total body surface area). Of 2,146 SNPs tested, a rare missense variant in the PTPN5 gene (rs56234898; minor allele frequency 1.5%) was significantly associated with decreased severity of post-burn HTS (P = 1.3×10(−6)). In gene-based analysis, PTPN5 (P = 1.2×10(−5)) showed a significant association and BDNF (P = 9.5×10(−4)) a borderline-significant association with HTS severity. CONCLUSIONS: We report PTPN5 as a novel genetic locus associated with HTS severity. PTPN5 is a MAPK inhibitor expressed in neurons, suggesting a potential role for neurotrophic factors and neuroinflammatory signaling in HTS pathophysiology.